Punctate inner choroidopathy: A review of the current diagnostic and therapeutic approaches - Kalogeropoulos, Dimitrios; Rahman, Najiha; Afshar, Farid; Hall, Nigel; Lotery, Andrew John (Progress in retinal and eye research, 2024)
Punctate inner choroidopathy (PIC) is an uncommon idiopathic inflammatory condition characterized by multifocal chorioretinopathy that primarily affects young adults, with a predilection for myopic females. Clinically, it manifests as small, yellowish-white lesions in the inner choroid and outer retina, often associated with inflammatory changes. Accurate diagnosis remains a challenge due to its resemblance to other posterior uveitic entities, necessitating an astute clinical eye and advanced imaging techniques for differentiation. Multimodal imaging plays a crucial role by offering valuable insights, as it enables the visualization of various abnormalities related to uveitis. The pathogenesis of PIC is still a subject of debate, with a complex interplay of genetic, immunological, and environmental factors proposed. Managing PIC presents multiple challenges for clinicians. Firstly, variable disease severity within and among patients requires diverse treatments, from observation to aggressive immunosuppression and/or anti-VEGF therapy. Secondly, treatment must distinguish between primary causes of vision loss. New or worsening PIC lesions suggest active inflammation, while new neovascular membranes may indicate secondary neovascular processes. Thirdly, deciding on maintenance therapy is complex, balancing PIC prognosis variability against immunosuppression risks. Some patients have long periods of inactivity and remission, while others face sudden, vision-threatening episodes during quiescent phases. Through a systematic review of the literature, this paper sheds light on the current understanding of PIC, its challenges, and the prospects for future research. By synthesizing existing knowledge, it aims to aid clinicians in accurate diagnosis and guide treatment decisions for improved visual outcomes in individuals affected by PIC.